The effect of heritability and host genetics on the gut microbiota and metabolic syndrome. Issue 6 (6th April 2016) - Lim, Mi Young; You, Hyun Ju; Yoon, Hyo Shin; Kwon, Bomi; Lee, Jae Yoon; Lee, Sunghee; Song, Yun-Mi; Lee, Kayoung; Sung, Joohon; Ko, GwangPyo
Abstract : Objective: Metabolic syndrome (MetS) arises from complex interactions between host genetic and environmental factors. Although it is now widely accepted that the gut microbiota plays a crucial role in host metabolism, current knowledge on the effect of host genetics on specific gut microbes related to MetS status remains limited. Here, we investigated the links among host genetic factors, gut microbiota and MetS in humans. Design: We characterised the gut microbial community composition of 655 monozygotic (n=306) and dizygotic (n=74) twins and their families (n=275), of which approximately 18% (121 individuals) had MetS. We evaluated the association of MetS status with the gut microbiota and estimated the heritability of each taxon. For the MetS-related and heritable taxa, we further investigated their associations with the apolipoprotein A-V gene ( APOA5 ) single nucleotide polymorphism (SNP) rs651821, which is known to be associated with triglyceride levels and MetS. Results: Individuals with MetS had a lower gut microbiota diversity than healthy individuals. The abundances of several taxa were associated with MetS status; Sutterella, Methanobrevibacter and Lactobacillus were enriched in the MetS group, whereas Akkermansia, Odoribacter and Bifidobacterium were enriched in the healthy group. Among the taxa associated with MetS status, the phylum Actinobacteria, to which Bifidobacterium belongs, had the highest heritability (45.7%). Even after adjustment for MetS status, reduced abundances of Actinobacteria and Bifidobacterium were significantly linked to the minor allele at the APOA5 SNP rs651821. Conclusions: Our results suggest that an altered microbiota composition mediated by a specific host genotype can contribute to the development of MetS.